Measuring the functional efficiency of capital markets - Johan E. Eklund; Sameeksha Desai (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
We apply the accelerator principle to measure the functional efficiency of capital markets. We estimate the elasticity of capital with respect to output using a panel of firms across 44 countries, and compare the results with existing approaches. Furthermore, we correlate our measure with corporate governance institutions.
Keywords: C00; G32; P00; 330; Allocation of capital; accelerator principle; functional efficiency; Finanzmarkt; Allokationseffizienz; Investition; Elastizität; Tobin's Q; Unternehmensentwicklung; Wertschöpfung; Corporate Governance; Schätzung; Welt